Holding fast - Brooke, Lauren; Copyright Paperback Collection (Library of Congress) (New York, NY : Scholastic, 2004)
Just when Amy feels that things are back to normal at Heartland, an injured police horse named Venture arrives. Venture's partner, Sergeant Garcia, is desperate to help the wounded gelding. Amy convinces the policeman to put his trust in Heartland's methods. But when Amy's tried-and-true remedies have no effect on Venture, she is the one who loses faith. Before she can reach a breakthrough, Amy must open herself up to new possibilities and learn to believe in the power of change.
G5
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; Children's stories